Paradise@Kundasang - Harbi, Muhd Hafis; Robert, Smith; Mohd Firdaus Abdullah Cham,, Mohd Norazizan; Sazalye Donol, Mohd Zulizzan (2018)
Paradise @Kundasang is the most refreshing concept of homestay coming soon to be located in Kampung Mata Mata Mesilau, Kundasang, Sabah that will serve both local and foreign tourists to experience a different environment of staying in a homestay. Our team pledge our full commitment in serving all guests with our very best and have them to enjoy an experience like no other. Our partnership business is built on the opportunity given by the Sabah gift of mother nature itself. The increasing number of foreign and local tourists visiting Sabah in the recent years have shown a sign of a need in the still developing tourism industry in Sabah. And interestingly we also managed to find out that the industry is very profitable not only for business carriers but were also will economically benefits the local people as it provides more job with better payment and also helps tp boost out infrastructures as well Tourists nowadays are different as they weren't only seeking for usual random things. They crave for a plus one services, which means they expect to get more with the money they are paying. This is the part where we. The Paradise (a Kundasang are formed for. We are not only going to serve our homestay guests with same random house staying experience where guest will only get good bed pillow and nice garden view balcony. We offer much much more than that. Well, literally speaking, it is a Paradise at Kundasang.